The Hemoglobin Bjgb From Bradyrhizobium diazoefficiens Controls NO Homeostasis in Soybean Nodules to Protect Symbiotic Nitrogen Fixation - Salas, Ana; Tortosa, Germán; Hidalgo-García, Alba; Delgado, Antonio; Bedmar, Eulogio J.; Richardson, David J.; Gates, Andrew J.; Delgado, María J. (Frontiers in Microbiology, 2020)
Legume-rhizobia symbiotic associations have beneficial effects on food security and nutrition, health and climate change. Hypoxia induced by flooding produces nitric oxide (NO) in nodules from soybean plants cultivated in nitrate-containing soils. As NO is a strong inhibitor of nitrogenase expression and activity, this negatively impacts symbiotic nitrogen fixation in soybean and limits crop production. In Bradyrhizobium diazoefficiens, denitrification is the main process involved in NO formation by soybean flooded nodules. In addition to denitrification, nitrate assimilation is another source of NO in free-living B. diazoefficiens cells and a single domain hemoglobin (Bjgb) has been shown to have a role in NO detoxification during nitrate-dependent growth. However, the involvement of Bjgb in protecting nitrogenase against NO in soybean nodules remains unclear. In this work, we have investigated the effect of inoculation of soybean plants with a bjgb mutant on biological nitrogen fixation. By analyzing the proportion of N in shoots derived from N2-fixation using the 15N isotope dilution technique we found that plants inoculated with the bjgb mutant strain had higher tolerance to flooding than those inoculated with the parental strain. Similarly, reduction of nitrogenase activity and nifH expression by flooding was less pronounced in bjgb than in WT nodules. These beneficial effects are probably due to the reduction of NO accumulation in bjgb flooded nodules compared to the wild-type nodules. This decrease is caused by an induction of expression and activity of the denitrifying nitric oxide reductase enzyme in bjgb bacteroids. As bjgb deficiency promotes NO-tolerance, the negative effect of NO on nitrogenase is partially prevented and thus demonstrates that inoculation of soybean plants with the B. diazoefficiens bjgb mutant confers protection of symbiotic nitrogen fixation during flooding.